The Relationship Between the Quarter-Life Crisis and Anxiety About Entering the Workforce Among Senior College Students - Florentina Pravista Alver Dwioknia; Berliana Henu Cahyani; Andreas Yudha Fery (Universitas Negeri Medan, 2026)
Anxiety about entering the workforce is one of the psychological problems commonly experienced by final-year university students as they transition from academic life to the professional world. One of the psychological factors presumed to be associated with this condition is the quarter-life crisis. This study aimed to empirically examine the relationship between quarter-life crisis and anxiety about entering the workforce among final-year students. The hypothesis proposed that there is a positive relationship between quarter-life crisis and anxiety about entering the workforce. This study employed a quantitative correlational research design. The sample was selected using a purposive sampling technique and consisted of 160 final-year students. The research instruments included the Quarter-Life Crisis Scale and the Workforce Entry Anxiety Scale, both of which met the validity and reliability requirements. Data were analyzed using the Pearson Product-Moment correlation technique with the assistance of Jamovi software. The results revealed a significant and very strong positive relationship between quarter-life crisis and anxiety about entering the workforce (r = 0.932, p < 0.001). Therefore, the proposed hypothesis was accepted. These findings indicate that the higher the level of quarter-life crisis experienced by students, the higher their anxiety about entering the workforce, and vice versa. The findings are expected to serve as a basis for universities in developing career guidance and psychological support programs to assist students in preparing for the transition into the workforce.